Efficacy of eltrombopag with immunosuppressive therapy for children with acquired aplastic anemia - Zhao, Yufei; Yang, Wenrui; Zhao, Xin; Hu, Xiangrong; Hu, Jing; Liu, Xu; Li, Jianping; Ye, Lei; Xiong, Youzhen; Yang, Yang; Zhang, Baohang; Li, Xiaoxia; et al. (Frontiers in Pediatrics, 2023)
Background: Eltrombopag (EPAG), an oral thrombopoietin receptor agonist (TPO-RA), has been proven to improve the hematologic response without increasing toxic effects as a first-line therapy combined with standard immunosuppressive treatment (IST) in adults with severe aplastic anemia (SAA). Nevertheless, the clinical evidence on the efficacy of EPAG in children with acquired aplastic anemia is limited and controversial. Methods: We performed a single-center, retrospective study to analyze the clinical outcomes of fifteen patients aged ≤18 years with newly diagnosed acquired SAA who received first-line IST and EPAG (EPAG group) compared with those of forty-five patients who received IST alone (IST group) by propensity score matching (PSM). Results: There was no difference in the overall response (OR) rate between the EPAG group and IST group (53.3% vs. 46.7% at 3 months, P=0.655; 66.7% vs. 57.8% at 6 months, P=0.543), but the complete response (CR) rate was statistically significant (20.0% vs. 4.4% at 3 months, P=0.094; 46.7% vs. 13.3% at 6 months, P=0.012). The median time to achieve a hematological response in the EPAG and IST groups was 105 days and 184 days, respectively. No difference was observed in the event-free survival (EFS) or overall survival (OS) rates. Conclusion: Adding EPAG to standard IST as the first-line treatment for children with acquired SAA improved the rapidity of hematological response and the CR rate but did not improve the OR or EFS rates.